Mean deflection angle, anterior and posterior length of the cranial base in Pakistani population with different sagittal skeletal malocclusion - Rana, Faiza; Faiza Malik (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the mean deflection angles as well as the anterior and posterior lengths of the cranial base in different skeletal patterns. Method: The cross-sectional study was conducted at the Department of Orthodontics, Sharif Medical and Dental College, Jati Umrah, Lahore, Pakistan, from December 2022 to May 2023, and comprised orthodontic patients of either gender aged 8-20 years. Pre-treatment lateral cephalograms of the patients were traced on lead acetate tracing sheet with 0.03mm mechanical pencil. Outcome variables for the cranial base nasion-sella-articulare, nasion-sella-basion nasion-sella and sella-to-basion angles were recorded, and data was stratified for age and gender. Data was analysed using SPSS 23. Results: Of the 93 patients, 60(64.5%) were females and 33(35.5%) were males. The overall mean age was 15.6±3.0 years, 38(40.9%) aged 8-14 years and 55(59.1%) aged 15-20 years). Mean values of cranial base flexion nasion-sella-articulare and nasion-sella-basion and posterior cranial base length sella-to-basion were significantly different sagittal patterns (p<0.05). Gender-based differences in mean values of anterior and posterior cranial base lengths were significant (p<0.05). Conclusion: Cranial base flexion decreased significantly. Cranial base lengths were higher for males than females, while age had no effect on cranial base morphology. Key Words: Cranial base, Craniofacial, Growth and development, Malocclusion, Mandible, Maxilla, Prognathism and retrognathia.